Impact of fluids on the mechanical properties and fracturing behavior of deep reservoir rocks - Zheng, Penglin; Xu, Ke; Zhang, Hui; Zhang, Zhizhen; Qiang, Jianli; Zhang, Yu; Chen, Qiuyu; Hu, Yixiong; Lai, Shujun (Frontiers in Earth Science, 2025)
The mechanical properties and fracturing behavior of deep reservoir rocks are significantly influenced by the presence of fluids, which is crucial for geomechanical evaluation and resource development efficiency. Based on a discrete element method (DEM) coupled with fluid-solid interaction modeling, this study systematically investigates the effects of different fluid types (water, oil, gas) and pore pressures on the mechanical characteristics and fracture evolution of rocks under deep reservoir conditions. The results indicate that fluid properties markedly alter the mechanical response of rocks. Water saturation induces the most significant deterioration in peak strength, with a degradation of 79.41% observed at a pore pressure of 120 MPa. In contrast, gas saturation leads to the greatest reduction in stiffness (Young’s modulus), with a maximum degradation of 46.47% under the high pore pressure of 120 MPa. Increasing pore pressure considerably reduces rock strength, and its weakening effect surpasses that caused by varying fluid types. However, the influence of fluid type on stiffness is more pronounced than that of pore pressure. At the microscopic scale, water weakens intergranular cementation through physical wedging and hydration reactions, promoting the development of shear fractures. Oil, due to its higher viscous resistance, causes localized stress concentrations and accelerates failure. The high compressibility of gas primarily affects the deformation capacity. This study reveals the differential degradation mechanisms of rock strength and deformation parameters under multiphase fluid conditions, providing a theoretical basis for the safe development of deep oil and gas resources.